2020
DOI: 10.21203/rs.3.rs-20406/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum A Proliferation-Inducing Ligand and MicroRNA-223 are Associated with Rheumatoid Arthritis: Diagnostic and Prognostic Implications

Abstract: Background: Current blood-based tests for rheumatoid arthritis (RA) have inherent limitations, necessitating the need for additional new biomarkers for its diagnosis and monitoring disease activity and responsiveness to therapy. microRNAs (miRNAs) and a proliferation-inducing ligand (APRIL) are deregulated in RA and were linked to its pathogenesis. This study investigated serum levels of APRIL, miR-223 and miR-155 in RA patients, their potential as diagnostic and prognostic biomarkers, and their correlation wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Rheumatoid arthritis (RA) is a chronic inflammatory disease. Studies have demonstrated that miR-223 is significantly higher in the plasma, serum and peripheral mononuclear cells (PBMCs) of RA patients than those of controls, indicating that miR-223 could be associated with the development, progression and severity of RA [92,93]. The reliability of the biological functions of miR-223 in RA has been confirmed by accurately measuring the AUC value, and sensitivity and specificity of miR-223 [94].…”
Section: Role Of Mir-223 In Rheumatoid Arthritismentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic inflammatory disease. Studies have demonstrated that miR-223 is significantly higher in the plasma, serum and peripheral mononuclear cells (PBMCs) of RA patients than those of controls, indicating that miR-223 could be associated with the development, progression and severity of RA [92,93]. The reliability of the biological functions of miR-223 in RA has been confirmed by accurately measuring the AUC value, and sensitivity and specificity of miR-223 [94].…”
Section: Role Of Mir-223 In Rheumatoid Arthritismentioning
confidence: 99%